Heterogeneity of the Stability of Messenger Ribonucleic Acid in Salmonella typhimurium - McClatchy, J. K. (1967)
Cells of Salmonella typhimurium strain SL 282, deflagellated by mechanical shear, regenerated their flagella in the absence of tryptophan, an amino acid required for growth but not found in flagellin. Ribonucleic acid (RNA) synthesis was severely inhibited by tryptophan starvation. These findings suggested that the messenger RNA (mRNA) for flagellin might be stable. Actinomycin D was used to inhibit RNA synthesis in ethylenediaminetetraacetate-treated bacteria. The introduction of an F(lac) episome into strain SL 282 permitted the simultaneous study of the synthesis of flagellin, β-galactosidase, and total protein. In the actinomycin-treated bacteria protein and β-galactosidase syntheses were inhibited by 90%, whereas flagellin synthesis was unaffected. We conclude that the mRNA for flagellin synthesis is stable and that species of mRNA vary with respect to metabolic stability in S. typhimurium.